Beyond Doing Good: An Interview with Dr. Kirsten Johnson on the Canadian Disaster and Humanitarian Response Training Program - Nouvet, Élysée (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
This text presents a synthesis of an interview with Dr. Kirsten Johnson, a Canadian physician fully engaged in training health professionals in humanitarian response and intervention. Dr. Johnson shows that simulation-based training is essential to the development of core humanitarian competencies and to the shaping of ethical attitudes as well. She stresses Canada’s duty to assure appropriate training of its health professionals before sending them out on humanitarian missions.